The Development of Kolej Kediaman Pagoh Freelancing System - Hasan Hisamudin, Siti Husna; Kamaruzaman, Danish Hakimi; Adnan, Amir Haziq; Kassim@kasim, Noordiana (Multidisciplinary Applied Research and Innovation, 2024)
KKP Freelancing System, designed exclusively for the residents of Pagoh Residential College, is a tailored website that connects talented freelancers within the college community, offering convenient access to a wide range of freelance services. The system utilizes various web technologies, including HTML, CSS, PHP, JavaScript, and Firebase. During the development process, Visual Studio Code served as the primary code editor, ensuring efficient programming tasks. For efficient database management, myphpAdmin was employed, providing a user-friendly interface for creating, editing, and organizing the system's data. Hosting the KKP Freelancing System was achieved using Firebase, a cloud-based hosting platform that delivered scalability, reliability, and fast performance. By combining the power of Visual Studio Code, myphpAdmin, and Firebase with other web technologies, the development team successfully created a reliable and user-friendly platform, fostering collaboration and supporting the local talent within the college community. Whether residents require assistance with academic projects, event organization, or personal tasks, KKP Freelancing System provides a thriving collaborative community to connect with skilled freelancers and achieve their goals.